2022
DOI: 10.35335/midwifery.v10i4.735
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of health promotion using social media on adolescent knowledge about Covid-19 in the work area of Health Center Batu Panjang, Rupat District, Bengkalis Regency

Abstract: Health promotion through teen social media can increase knowledge about Covid-19 by 95% and influence behavior to prevent Covid-19 by 77%. The aim of this study was to determine the effectiveness of the use of social media for health promotion on youth Covid-19 knowledge in the workplace at Batu Panjang Health Centre, Rupat District, Bengalis Regency in 2021. This type of research is quantitative analysis with a quasi-experimental design. The population for this study was all 12th graders at Rupat High School,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Health promotion through social media can bring lifestyle changes in our communities. Studies have shown that social media can be used as effective platforms for not only spreading awareness about different health issues but also enabling community members to make an informed decisions in matters related to their health [13][14][15][16][17][18] . Through having different accounts, groups, or pages in social media like twitter, LinkedIn, Facebook, WhatsApp, and others, students will bring significant changes to the public.…”
Section: Role Of Medical Students In Community Lifestyle Transformationmentioning
confidence: 99%
“…Health promotion through social media can bring lifestyle changes in our communities. Studies have shown that social media can be used as effective platforms for not only spreading awareness about different health issues but also enabling community members to make an informed decisions in matters related to their health [13][14][15][16][17][18] . Through having different accounts, groups, or pages in social media like twitter, LinkedIn, Facebook, WhatsApp, and others, students will bring significant changes to the public.…”
Section: Role Of Medical Students In Community Lifestyle Transformationmentioning
confidence: 99%